Analisis Efektivitas Dan Kontribusi Penerimaan Pajak Bumi Dan Bangunan Terhadap Pendapatan Daerah Di Kota Bandung - Yulia Anggara Sari (Center fo State Civil Apparatus Training and Development and Competency Mapping, 2010)
Efectivity of tax revenue can be an indicator of performance in Dinas Pendapatan (Dipenda) Kota Bandung. Tax revenue had called efective if the acceptance fit to the real potention. The aim of this research is to gain knowledge the efectivity of land and building tax revenue based on tax target and contribution toward local revenue in Bandung City. This research using descriptive method, using APBD Kota Bandung from 2002 to 2008 as main data source. The result show that (1) efectivity of land and building tax revenue rate from 2002 to 2008, had fluctuative condition with average of 99,07% that include in efective criteria. (2) growth rate of area income in Bandung City from 2002 to 2008 average of 15,92%. (3) contribution of land and building tax toward local revenue in average 6,15% that means bad contribution. The recomendation highlights the importance of repeating datacheck to subject dan object of land and building tax so the result can be significant and increasing local revenue to finance the government activity.